HIV and breastfeeding: breastfeeding promotion and support - Jamani, Nurjasmine Aida (2014)
Current policy on HIV mothers (Pekeliling Ketua Pengarah Kesihatan Bil 5/2002) –The Government is committed in promoting, protecting and supporting breastfeeding in Malaysia. –However due to the risk of transmission of HIV through breast milk, babies born to mothers who are HIV positive will not be given breast milk. –Infant formula will be provided for these babies. –On discharge from the hospital, mothers with family income of less than RM1200 per month will be provided with infant formula for up to six months.